2016
DOI: 10.3892/mco.2016.954
|View full text |Cite
|
Sign up to set email alerts
|

Clinical features and outcomes of patients with lung cancer as well as combined pulmonary fibrosis and emphysema

Abstract: Abstract. The syndrome of combined pulmonary fibrosis and emphysema (CPFE) has been characterized by severely impaired gas exchange and poor survival. However, the clinical features of patients with lung cancer plus CPFE have remained elusive. The present study performed a retrospective analysis to examine the clinical characteristics and outcome of surgically resected patients with lung cancer plus CPFE. Among 831 patients with primary lung cancer who underwent surgical resection, 23 patients (2.8%) were diag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
25
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(30 citation statements)
references
References 16 publications
3
25
0
2
Order By: Relevance
“…Like previously reported, cancer had mainly subpleural localization, in the lower lobes, while in patients with emphysema -in the upper lobes [36][37][38]. Furthermore, a 5-year survival rate did not differ between the CPFE and IPF group (22% and 22%, respectively) [39]. Similar results were reported by Sato et al [40].…”
Section: Introductionsupporting
confidence: 84%
See 1 more Smart Citation
“…Like previously reported, cancer had mainly subpleural localization, in the lower lobes, while in patients with emphysema -in the upper lobes [36][37][38]. Furthermore, a 5-year survival rate did not differ between the CPFE and IPF group (22% and 22%, respectively) [39]. Similar results were reported by Sato et al [40].…”
Section: Introductionsupporting
confidence: 84%
“…Interestingly, according to scarce data, squamous cell cancer followed by adenocarcinoma were the most common types in the CPFE group [39,40]. In the IPF group, that sequence may be reversed [39,40,42].…”
Section: Introductionmentioning
confidence: 99%
“…Several previous studies showed lung cancer in patients with CPFE was advanced stage (10,14), while other studies indicated that more lung cancer patients with CPFE were early stage (11)(12)(13)(15)(16)(17)(18)(19)(20)(21)(22). Pulmonary function test was conducted in several studies, and the results have varied (11)(12)(14)(15)(16)(17)(18)(19)(20)(21)(22). CPFE was an independent factor for a poor prognosis in lung cancer patient with CPFE (11,18,21).…”
Section: Introductionmentioning
confidence: 96%
“…In three previous studies of lung cancer patients with CPFE adenocarcinoma was the most common type of cancer, followed by squamous cell carcinoma (10)(11)(12). However, other studies had shown that squamous cell carcinoma was the most common type of cancer (13)(14)(15)(16)(17)(18)(19)(20)(21)(22). Several previous studies showed lung cancer in patients with CPFE was advanced stage (10,14), while other studies indicated that more lung cancer patients with CPFE were early stage (11)(12)(13)(15)(16)(17)(18)(19)(20)(21)(22).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation